Environment-friendly moisture-proof high-speed cigarette adhesive and preparation method thereof

By using corn starch co-precipitation composite modified crosslinked soy protein and other components, the existing problems of slow curing and harmful substances under high-speed production conditions are solved, and rapid curing, strong bonding and good waterproofing performance are achieved.

CN119570398AActive Publication Date: 2025-03-07ZHENGZHOU SHENHUO JIAOJI CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411734357.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-07
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing cigarette glue cannot meet the needs of rapid curing and strong bonding under high-speed production conditions. It also has volatile and semi-volatile harmful substances, and has poor water resistance.

Method used

Corn starch co-precipitation composite modified cross-linked soy protein, polyacrylic acid, polyvinyl alcohol, hydroxyethyl cellulose, potassium sorbate, sodium dodecyl sulfate and urea-formaldehyde resin are used to prepare an environmentally friendly, moisture-proof high-speed cigarette glue.

Benefits of technology

It realizes rapid curing and strong bonding of environmentally friendly high-speed cigarette glue, with excellent water solubility and stability, low content of volatile organic compounds, good adhesion and waterproof and moisture-proof performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of cigarette adhesives, and particularly relates to an environment-friendly moisture-proof high-speed cigarette adhesive and a preparation method thereof. The environment-friendly moisture-proof high-speed cigarette adhesive is prepared from the following components in percentage by weight: 10-15% of corn starch coprecipitation composite modified crosslinked soybean protein, 1-3% of polyacrylic acid, 1-3% of polyvinyl alcohol, 2-5% of hydroxyethyl cellulose, 0.5-1% of potassium sorbate, 0.5-1% of lauryl sodium sulfate, 2-5% of urea resin, 60-70% of VAE emulsion and the balance of water. The environment-friendly moisture-proof high-speed cigarette adhesive has excellent water solubility and stability, is extremely low in volatile organic compound content, can provide good adhesive force on different surfaces, ensures the structural stability of cigarettes, has a relatively high moisture evaporation speed, can be rapidly cured in a cigarette production line, and has a good application prospect. Meanwhile, very excellent hydrostatic pressure resistance and good waterproof and moistureproof performance are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cigarette adhesives, and in particular relates to an environmentally friendly moisture-proof high-speed cigarette adhesive and a preparation method thereof. Background Art

[0002] High-speed cigarette glue is a special adhesive used in cigarette production. It is usually used to bond cigarette paper, tobacco, filter tips and other components to ensure the stability and integrity of cigarette products. With the advancement of cigarette production technology, the demand for cigarette glue has also changed, especially the application on high-speed, automated production lines, which has prompted the continuous development of cigarette glue technology. With the continuous expansion of global cigarette production, cigarette production has gradually achieved automation and assembly line operation, and the production speed has been greatly improved. In order to meet the requirements of high-speed production, the performance of adhesives must be greatly improved so that the bonding work can be completed in a shorter time without affecting the quality of cigarettes. Traditional cigarette glue is usually water-based glue or solvent-based glue. Although they work well in lower-speed production lines, they often cannot meet the needs of rapid curing and strong bonding under high-speed production conditions. Therefore, the research and development of high-speed cigarette glue has become an important part of the technological progress of the cigarette industry.

[0003] With the strictness of environmental protection regulations, traditional solvent-based adhesives are gradually being eliminated and replaced by environmentally friendly adhesives such as water-based adhesives and solvent-free adhesives. These adhesives not only meet environmental protection standards, but also do not release harmful volatile organic compounds during the production process. The Chinese patent with publication number CN107502229A discloses a nanocrystalline cellulose enhanced oxidized modified corn starch cigarette glue and a preparation method. It uses cellulose oxidized modified corn starch to obtain a biomass cigarette glue. The cigarette glue has the advantages of fast drying speed and good film-forming properties, but it still contains volatile and semi-volatile harmful substances. The Chinese patent with publication number CN1 10872478A discloses a low-viscosity high-speed cigarette glue and a preparation method. The cigarette glue prepared by it has the advantages of low viscosity and good dispersibility, but its drying time is too long, it is not stable enough after dilution, and its water resistance is poor.

[0004] In view of the above technical defects, a solution is now proposed. Summary of the invention

[0005] The purpose of the present invention is to provide an environmentally friendly moisture-proof high-speed cigarette adhesive and a preparation method thereof. The environmentally friendly high-speed cigarette adhesive of the present invention meets the health standards of the cigarette adhesive industry, contains very little harmful substances, dries quickly and has excellent waterproof performance.

[0006] To achieve the above object, the present invention adopts the following technical scheme: an environmentally friendly moisture-proof high-speed cigarette adhesive is composed of the following percentage components: 10-15% corn starch co-precipitated composite modified cross-linked soybean protein, 1-3% polyacrylic acid, 1-3% polyvinyl alcohol, 2-5% hydroxyethyl cellulose, 0.5-1% potassium sorbate, 0.5-1% sodium lauryl sulfate, 2-5% urea-formaldehyde resin, 60-70% VAE emulsion and the balance water;

[0007] The preparation method of corn starch co-precipitated composite modified cross-linked soybean protein comprises the following steps:

[0008] A1: Add corn starch into pure water, set the stirrer speed to 800-900 rpm and stir for 30 minutes;

[0009] A2: Add soy protein to pure water and set the stirrer speed to 800-900 rpm for 30 minutes;

[0010] A3: Mix the dissolved corn starch and dissolved soy protein, stir gently with a glass rod, stop stirring after 5 minutes, let it stand for 15 minutes, and use pH test paper to detect the pH value of the corn starch and soy protein mixture after standing. Use acetic acid and ammonia water to adjust the pH value of the mixture to between 4.2-4.8;

[0011] A4: After pH adjustment, let stand for 15 minutes. After standing, add coupling agent N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane. At the same time, adjust the stirrer speed to 400-500 rpm and stir for 30 minutes.

[0012] A5: Adjust the reaction temperature to 12-15℃. At this time, the corn starch and soybean protein in the solution will co-precipitate through hydrogen bonding and electrostatic force. Keep the reaction temperature for 30-40 minutes.

[0013] A6: Use filter paper to separate the composite precipitate and deionized water. After separation, use deionized water to wash the unreacted soy protein and corn starch. Repeat the separation and washing 1-2 times.

[0014] A7: Put the washed composite precipitate into a drying oven, set the drying temperature to 55-60°C, dry for 4-6 hours, then add the dried composite precipitate into a grinder, grind for 45-60 minutes to obtain corn starch co-precipitated composite modified soy protein;

[0015] Furthermore, in step A1, the mass ratio of corn starch to deionized water is 1:50; in step A2, the mass ratio of corn starch to deionized water is 1:50; in step A3, the mass ratio of dissolved corn starch to dissolved soy protein is 1:1; and in step A4, the coupling agent is N-aminoethyl-3-aminopropylmethyldimethoxysilane, wherein the mass ratio of the coupling agent to the mixed corn starch and soy protein mixture is 1:50.

[0016] Furthermore, a method for preparing an environmentally friendly moisture-proof high-speed cigarette adhesive comprises the following steps:

[0017] B1: Add corn starch co-precipitated composite modified cross-linked soybean protein, hydroxyethyl cellulose and urea-formaldehyde resin into deionized water, adjust the stirrer speed to 600-800 rpm, adjust the reaction temperature to 60-65°C, stir and dissolve for 45 minutes to obtain product A;

[0018] B2: Add polyacrylic acid, polyvinyl alcohol and VAE emulsion into deionized water, adjust the stirrer speed to 600-800 rpm, adjust the reaction temperature to 45-50°C, and stir and dissolve for 45 minutes to obtain product B;

[0019] B3: Mix product A and product B and add them into a reactor, add potassium sorbate and sodium dodecyl sulfate at the same time, adjust the stirrer speed to 300-400 rpm, adjust the reaction temperature to 65-70°C, stir the reaction for 1-1.5 hours and then let it stand for 15 minutes to obtain an environmentally friendly moisture-proof high-speed cigarette adhesive.

[0020] Furthermore, the VAE emulsion is an aqueous vinyl acetate-ethylene copolymer emulsion; the hydroxyethyl cellulose is a water-soluble hydroxyethyl cellulose with a density of 7000-9000 g / cm 3 The urea-formaldehyde resin is a melamine-modified water-soluble urea-formaldehyde resin powder with a density of 1.17 g / cm 3 .

[0021] In summary, due to the adoption of the above technical scheme, the beneficial effects of the present invention are that the environmentally friendly moisture-proof high-speed cigarette adhesive of the present invention has excellent water solubility and stability, extremely low volatile organic compound content, can provide good adhesion on different surfaces, ensure the structural stability of cigarettes, has a faster water evaporation rate, can achieve rapid curing in the cigarette production line, and at the same time has very excellent resistance to hydrostatic pressure and good waterproof and moisture-proof properties. DETAILED DESCRIPTION

[0022] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific examples.

[0023] The experimental methods in the following examples, unless otherwise specified, are conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0024] Example 1

[0025] 1: Add 50g corn starch into 2.5L pure water, set the stirrer speed to 900rpm and stir for 30min;

[0026] 2: Add 50g soy protein into 2.5L pure water, set the stirrer speed to 900rpm and stir for 30min;

[0027] 3: Mix 2kg of dissolved corn starch and 2kg of dissolved soy protein, stir gently with a glass rod, stop stirring after 5 minutes, let it stand for 15 minutes, and use pH test paper to detect the pH value of the mixed corn starch and soy protein mixture after standing. Use acetic acid and ammonia water to adjust the pH value of the mixture to 4.4;

[0028] 4: After pH adjustment, let stand for 15 minutes. After standing, add 80g of coupling agent N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, adjust the stirrer speed to 500rpm, and stir for 30 minutes;

[0029] 5: Adjust the reaction temperature to 15°C. At this time, the corn starch and soybean protein in the solution undergo a coprecipitation reaction through hydrogen bonding and electrostatic forces. Maintain the reaction temperature for 40 minutes.

[0030] 6: Use filter paper to separate the composite precipitate and deionized water. After separation, use deionized water to wash the unreacted soy protein and corn starch. Repeat the separation and washing twice;

[0031] 7: Put the washed composite precipitate into a drying oven, set the drying temperature to 60° C., dry for 6 hours, then add the dried composite precipitate into a grinder, grind for 60 minutes to obtain the corn starch co-precipitated composite modified soybean protein prepared in Example 1;

[0032] Table 1, reagent parameters used in Example 1

[0033]

[0034] Example 2

[0035] 1: Add 100g corn starch into 5L pure water, set the stirrer speed to 800rpm and stir for 30min;

[0036] 2: Add 100g soy protein into 5L pure water, set the stirrer speed to 800rpm and stir for 30min;

[0037] 3: Mix 1kg of dissolved corn starch and 1kg of dissolved soy protein, stir gently with a glass rod, stop stirring after 5 minutes, let it stand for 15 minutes, and use pH test paper to detect the pH value of the mixed corn starch and soy protein mixture after standing. Use acetic acid and ammonia water to adjust the pH value of the mixture to between 4.8;

[0038] 4: After pH adjustment, let stand for 15 minutes. After standing, add 40g of coupling agent N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, adjust the stirrer speed to 500rpm, and stir for 30 minutes;

[0039] 5: Adjust the reaction temperature to 12°C. At this time, the corn starch and soybean protein in the solution undergo a coprecipitation reaction through hydrogen bonding and electrostatic forces. Maintain the reaction temperature for 40 minutes.

[0040] 6: Use filter paper to separate the composite precipitate and deionized water. After separation, use deionized water to wash the unreacted soy protein and corn starch. Repeat the separation and washing twice;

[0041] 7: Put the washed composite precipitate into a drying oven, set the drying temperature to 58° C., dry for 6 hours, then add the dried composite precipitate into a grinder, grind for 60 minutes to obtain the corn starch co-precipitated composite modified soybean protein prepared in Example 2;

[0042] Table 2, reagent parameters used in Example 2

[0043]

[0044] Example 3

[0045] 1: 30 g of the corn starch co-precipitated composite modified cross-linked soybean protein prepared in Example 1, 10 g of hydroxyethyl cellulose and 10 g of urea-formaldehyde resin were added into 7 ml of deionized water, the stirrer speed was adjusted to 800 rpm, the reaction temperature was adjusted to 65° C., and the mixture was stirred and dissolved for 45 min to obtain product A;

[0046] 2: Add 6 g polyacrylic acid, 6 g polyvinyl alcohol and 120 g VAE emulsion into 7 ml deionized water, adjust the stirrer speed to 800 rpm, adjust the reaction temperature to 50 ° C, stir and dissolve for 45 minutes to obtain product B;

[0047] 3: Product A and product B were mixed and added into a reactor, and 2 g of potassium sorbate and 2 g of sodium dodecyl sulfate were added at the same time. The stirrer speed was adjusted to 400 rpm, and the reaction temperature was adjusted to 70°C. The mixture was stirred for 1.5 h and then allowed to stand for 15 min to obtain an environmentally friendly moisture-proof high-speed cigarette adhesive prepared in Example 3.

[0048] Table 3, reagent parameters used in Example 3

[0049] Drug Name source model parameter Polyacrylic acid Changzhou Runyang Chemical Co., Ltd. GY-303 200ml Polyvinyl alcohol Langfang Feitai New Material Technology Co., Ltd. 2488-5 500g Hydroxyethyl Cellulose Sichuan Lanyang Daily Chemical Co., Ltd. XH-666 1kg Potassium Sorbate Henan Jianchang Chemical Co., Ltd. 012 1kg Sodium Lauryl Sulfate Langfang Pengcai Chemical Co., Ltd. 151-21-3 25kg Urea-formaldehyde resin Langfang Senbang Chemical Co., Ltd. SB-02 1kg VAE Emulsion Shandong Kejian Chemical Co., Ltd. 41242 5kg

[0050] Example 4

[0051] 10-15% corn starch co-precipitated composite modified cross-linked soybean protein, 1-3% polyacrylic acid, 1-3% polyvinyl alcohol, 2-5% hydroxyethyl cellulose, 0.5-1% potassium sorbate, 0.5-1% sodium lauryl sulfate, 2-5% urea-formaldehyde resin, 60-70% VAE emulsion and water as the balance

[0052] 1: 20 g of the corn starch co-precipitated composite modified cross-linked soybean protein prepared in Example 2, 4 g of hydroxyethyl cellulose and 4 g of urea-formaldehyde resin were added into deionized water, the stirrer speed was adjusted to 800 rpm, the reaction temperature was adjusted to 65° C., and the mixture was stirred and dissolved for 45 min to obtain product A;

[0053] 2: Add 4g polyacrylic acid, 4g polyvinyl alcohol and 140g VAE emulsion into deionized water, adjust the stirrer speed to 600-800rpm, adjust the reaction temperature to 45-50℃, stir and dissolve for 45min to obtain product B;

[0054] 3: Mix product A and product B and add them into the reactor, add 1g potassium sorbate and 1g sodium dodecyl sulfate at the same time, adjust the stirrer speed to 400rpm, adjust the reaction temperature to 70°C, stir the reaction for 1h and then let it stand for 15min to obtain an environmentally friendly moisture-proof high-speed cigarette adhesive prepared in Example 4.

[0055] Table 4, reagent parameters used in Example 4

[0056] Drug Name source model parameter Polyacrylic acid Changzhou Runyang Chemical Co., Ltd. GY-303 200ml Polyvinyl alcohol Langfang Feitai New Material Technology Co., Ltd. 2488-5 500g Hydroxyethyl Cellulose Sichuan Lanyang Daily Chemical Co., Ltd. XH-666 1kg Potassium Sorbate Henan Jianchang Chemical Co., Ltd. 012 1kg Sodium Lauryl Sulfate Langfang Pengcai Chemical Co., Ltd. 151-21-3 25kg Urea-formaldehyde resin Langfang Senbang Chemical Co., Ltd. SB-02 <![CDATA[1k g ]]> VAE Emulsion Shandong Kejian Chemical Co., Ltd. 41242 5kg

[0057] Comparative Example 1

[0058] The specific implementation method of the Chinese patent with publication number CN107502229A was selected as comparative example 1.

[0059] Comparative Example 2

[0060] Example 1 of the Chinese patent with publication number CN1 10872478A was selected as comparative example 2.

[0061] Physical performance test:

[0062] The conventional performance parameters of Example 3, Example 4, Comparative Example 1 and Comparative Example 2 were subjected to physical performance tests: cotton cloth was selected as the test substrate, and the peel strength of Example 3, Example 4, Comparative Example 1 and Comparative Example 2 was tested after being coated on the cotton cloth substrate for 30 seconds; the dilution stability was tested according to the high-speed cigarette adhesive dilution stability test method specified in "YC / T188-2004 High-speed Cigarette Adhesive", and the shear thinning index was tested according to the method of "Testing the Rheological Properties of Non-Newtonian Materials by Rotational Viscometer" specified in Appendix B of "ASTM D2196-2015 Standard Test Method" for Example 3, Example 4, Comparative Example 1 and Comparative Example 2;

[0063] Table 5, conventional physical properties test results:

[0064] Viscosity (mpa·S) Solid content (%) pH Dry time Example 3 300 48.4 4.5 5 minutes 45 seconds Example 4 300 48.7 4.5 5 minutes 50 seconds Comparative Example 1 400 50.4 4.6 6 minutes 30 seconds Comparative Example 2 200 50.6 4.7 6 minutes 45 seconds

[0065] Table 6, Physical properties test results

[0066] Film resolubility Initial adhesion Dilution stability Shear Thinning Index Example 3 3 seconds, dissolved 0.58N / 20mm 3% 1.04 Example 4 3 seconds, dissolved 0.59N / 20mm 3% 1.03 Comparative Example 1 4 seconds, dissolved 0.54N / 20mm 3% 1.06 Comparative Example 2 5 seconds, dissolved 0.52N / 20mm 3.6% 1.08

[0067] Cigarette adhesive waterproof performance test

[0068] According to the relevant provisions of ISO 811-1981, the prepared cigarette glue was tested for waterproof performance using a hydrostatic pressure tester. Six cigarette glue samples were taken from each of Example 3, Example 4, Comparative Example 1 and Comparative Example 2, and the results were averaged. The water pressure rising rate was 0.59 kPa / min, and the water temperature was 20°C. After the samples were humidified under standard atmospheric conditions as required, the cigarette glue test surface was contacted with water, and increasing water pressure was applied to the samples. The water seepage phenomenon was continuously observed, and the hydrostatic pressure value at the third water seepage on the cigarette glue was recorded. The test was repeated and the average value was taken. The larger the result, the better the anti-hydrostatic pressure performance.

[0069] Table 7, Waterproof performance test results

[0070]

[0071]

[0072] From the analysis of Table 7, it can be seen that the cigarette adhesives prepared in Examples 3 and 4 have very excellent waterproof performance in the waterproof performance test, and can withstand a hydrostatic pressure value of 8 kPa under standard atmospheric pressure conditions.

[0073] Test of harmful substances in cigarette glue

[0074] Table 8, Volatile and semi-volatile organic matter content test

[0075]

[0076] Table 9, Inorganic element content

[0077]

[0078] By analyzing Table 8 and Table 9, it can be seen that the cigarette adhesive prepared in Example 3 and Example 4 meets the cigarette adhesive hygiene standard (MK / JS517-2010) issued by the Chinese cigarette industry.

[0079] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. An environmentally friendly moisture-proof high-speed cigarette adhesive, characterized in that: The invention is composed of the following percentage ingredients: 10-15% corn starch co-precipitated composite modified cross-linked soybean protein, 1-3% polyacrylic acid, 1-3% polyvinyl alcohol, 2-5% hydroxyethyl cellulose, 0.5-1% potassium sorbate, 0.5-1% sodium lauryl sulfate, 2-5% urea-formaldehyde resin, 60-70% VAE emulsion and the balance water; The preparation method of corn starch co-precipitated composite modified cross-linked soybean protein comprises the following steps: A1: Add corn starch into pure water, set the stirrer speed to 800-900 rpm and stir for 30 minutes; A2: Add soy protein to pure water and set the stirrer speed to 800-900 rpm for 30 minutes; A3: Mix the dissolved corn starch and dissolved soy protein, stir gently with a glass rod, stop stirring after 5 minutes, let it stand for 15 minutes, and use pH test paper to detect the pH value of the corn starch and soy protein mixture after standing. Use acetic acid and ammonia water to adjust the pH value of the mixture to between 4.2-4.8; A4: After pH adjustment, let stand for 15 minutes. After standing, add coupling agent N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane. At the same time, adjust the stirrer speed to 400-500 rpm and stir for 30 minutes. A5: Adjust the reaction temperature to 12-15℃. At this time, the corn starch and soybean protein in the solution will co-precipitate through hydrogen bonding and electrostatic force. Keep the reaction temperature for 30-40 minutes. A6: Use filter paper to separate the composite precipitate and deionized water. After separation, use deionized water to wash the unreacted soy protein and corn starch. Repeat the separation and washing 1-2 times. A7: Put the cleaned composite precipitate into a drying oven, set the drying temperature to 55-60°C, dry for 4-6 hours, then add the dried composite precipitate into a grinder, grind for 45-60 minutes to obtain corn starch co-precipitated composite modified soy protein.

2. The environmentally friendly moisture-proof high-speed cigarette adhesive according to claim 1, characterized in that: The mass ratio of corn starch to deionized water in step A1 is 1:

50.

3. The environmentally friendly moisture-proof high-speed cigarette adhesive according to claim 1, characterized in that: The mass ratio of corn starch to deionized water in step A2 is 1:

50.

4. The environmentally friendly moisture-proof high-speed cigarette adhesive according to claim 1, characterized in that: The mass ratio of the dissolved corn starch to the dissolved soybean protein in step A3 is 1:

1.

5. The environmentally friendly moisture-proof high-speed cigarette adhesive according to claim 1, characterized in that: The coupling agent in step A4 is N-aminoethyl-3-aminopropylmethyldimethoxysilane, wherein the mass ratio of the coupling agent to the mixed corn starch and soybean protein mixture is 1:

50.

6. The environmentally friendly moisture-proof high-speed cigarette adhesive according to claim 1, characterized in that: The VAE emulsion is an aqueous vinyl acetate-ethylene copolymer emulsion.

7. The environmentally friendly moisture-proof high-speed cigarette adhesive according to claim 1, characterized in that: The hydroxyethyl cellulose is water-soluble hydroxyethyl cellulose with a density of 7000-9000g / cm 3 .

8. The environmentally friendly moisture-proof high-speed cigarette adhesive according to claim 1, characterized in that: The urea-formaldehyde resin is melamine-modified water-soluble urea-formaldehyde resin powder with a density of 1.17 g / cm 3 .

9. The method for preparing an environmentally friendly moisture-proof high-speed cigarette adhesive according to claim 1, characterized in that: The following steps are involved: B1: Add corn starch co-precipitated composite modified cross-linked soybean protein, hydroxyethyl cellulose and urea-formaldehyde resin into deionized water, adjust the stirrer speed to 600-800 rpm, adjust the reaction temperature to 60-65°C, stir and dissolve for 45 minutes to obtain product A; B2: Add polyacrylic acid, polyvinyl alcohol and VAE emulsion into deionized water, adjust the stirrer speed to 600-800 rpm, adjust the reaction temperature to 45-50°C, and stir and dissolve for 45 minutes to obtain product B; B3: Mix product A and product B and add them into a reactor, add potassium sorbate and sodium dodecyl sulfate at the same time, adjust the stirrer speed to 300-400 rpm, adjust the reaction temperature to 65-70°C, stir the reaction for 1-1.5 hours and then let it stand for 15 minutes to obtain an environmentally friendly moisture-proof high-speed cigarette adhesive.

Citation Information

Patent Citations

  • Nanometer crystalline cellulose-enhanced oxidizing modified corn starch cigarette adhesive and preparation method

    CN107502229A

  • Low-viscosity high-speed cigarette adhesive and preparation method thereof

    CN110872478A

  • Aqueous adhesive without aldehyde and preparation method

    CN101092549A

  • Preparation method for environment-friendly starch-based binder

    CN102367367A

  • Urea-formaldehyde resin adhesive containing modified starch emulsion, preparation method and application

    CN107236498A